PENGARUH SUBSTITUSI TEPUNG PISANG KEPOK DAN PUREE LABU KUNING TERHADAP DAYA TERIMA SERTA KANDUNGAN KARBOHIDRAT DAN VITAMIN C PADA KUE BINGKANG - Khalisa, Dian; Khazanah, Wiqayatun (JURNAL RISET GIZI, 2022)
Background: Indonesia is a country that has abundant local food ingredients. One of the local food ingredients that can be utilized and processed into bingkang cake is banana flour and pumpkin. Banana and pumpkin flour have good nutritional value for health. In addition to utilizing local food, this substitution of banana and pumpkin flour can also increase the nutritional value of bingkang cake.Objective: To determine the effect of substitution of banana kepok flour and pumpkin puree on the acceptability and content of carbohydrates and vitamin C in bingkang cake.Research Methods: This research is an experimental study, with the experimental design used is a completely randomized design, 3 treatments and 3 repetitions. Data processing and analysis was carried out using ANOVA (Analysis of Variance) andfurther Duncan's multiple testtest.Results : The substitution of banana kepok flour and pumpkin puree 25%, 50% and 75% significantly affected the organoleptic properties with a significant level (P value 0.05). On average, the panelists gave an assessment of likes and dislikes the taste, aroma, color and texture of the bingkang cake. The results of the analysis of the highest carbohydrate content were in the 75% treatment and the highest Vitamin C content was in the 25% treatment.Conclusion : The substitution of banana kepok flour and pumpkin puree has a significant effect on the texture, taste, aroma and color of the bingkang cake.Suggestion: It is hoped that further research will be conducted on the chemical properties of bingkang cake substituted with kepok banana flour and pumpkin puree.